Potential Immune-Related Adverse Events Associated With Monotherapy and Combination Therapy of Ipilimumab, Nivolumab, and Pembrolizumab for Advanced Melanoma: A Systematic Review and Meta-Analysis - Almutairi, Abdulaali R.; McBride, Ali; Slack, Marion; Erstad, Brian L.; Abraham, Ivo (Frontiers in Oncology, 2020)
Background: The use of ipilimumab, nivolumab, and pembrolizumab as monotherapies or in combination has transformed the management of advanced melanoma even though these drugs are associated with a new profile of immune-related adverse events (irAEs). The incidence of irAEs from clinical trials of these agents is an important factor for clinicians when treating patients with advanced melanoma. In the current study, we aimed to profile the incidence of potential irAEs of these agents when used as monotherapy and as combination therapy. Methods: We searched the Medline, Embase, and Cochrane databases; clinicaltrials.gov; and websites of regulatory agencies in the USA, Europe, Australia, and Japan for phase 1-3 trials of ipilimumab, nivolumab, and pembrolizumab for advanced melanoma. Random effect meta-analysis was utilized to profile the incidence of potential irAEs. Results: A total of 58 reports of 35 trials including 6331 patients with advanced melanoma and reporting irAE data were included in the meta-analyses. We found higher incidences of potential irAEs in combination therapies versus monotherapies for most of the types of irAEs. Among the monotherapies, ipilimumab users had the most frequent incidence of potential irAEs related to the gastrointestinal system (diarrhea, 29%; and colitis, 8%) and skin (rash, 31%; pruritus, 27%; and dermatitis, 10%), with hypophysitis in 4% of the patients. The most frequent potential irAEs among nivolumab users were maculopapular rash (13%), erythema (4%), hepatitis (3%), and infusion-related reactions (3%), while they were arthralgia (12%), hypothyroidism (8%), hyperglycemia (6%), and diabetes mellitus (2%) among pembrolizumab users. Conclusion: Especially the combination therapies tend to elevate the incidence of potential irAEs. Clinicians should be vigilant about irAEs following combination therapy as well as gastrointestinal and skin irAEs following ipilimumab therapy, in addition to being aware of potential irAEs leading to diabetes, thyroid, hepatic, and musculoskeletal disorders following nivolumab and pembrolizumab therapy.